Targeted Therapy-induced Facial Skin Toxicities: Impact on Quality of Life in Cancer Patients - Kaori Yagasaki; Hiroko Komatsu; Kenzo Soejima; Katsuhiko Naoki; Ichiro Kawada; Hiroyuki Yasuda; Yasuo Hamamoto (Elsevier, 2018)
Objective: Targeted therapy-induced facial skin toxicities may reduce overall quality of life (QoL) in cancer patients. We investigated whether facial skin toxicities affect QoL and attempted to identify factors related to QoL in patients with advanced/recurrent cancer. Methods: We performed a cross-sectional study in 34 outpatients with advanced/recurrent cancer showing targeted therapy-induced facial skin toxicities in Japan between November 2016 and February 2017. For measurement, we used the Kessler Psychological Distress Scale (K6), Mental Adjustment to Cancer (MAC) Scale, and Dermatology Life Quality Index (DLQI). Data were analyzed using Spearman's rank correlation coefficient. Results: Mean DLQI score in 34 patients was 4.59 (standard deviation ± 4.70), which was interpreted as a small effect on a patient's life. Acneiform rash was the most common skin condition noted, followed by xerosis, pruritus, and erythema. Analysis of DLQI scores revealed that symptoms and feelings was the domain most commonly affected among different domains constituting the DLQI. MAC analysis revealed that the fighting spirit score was the highest among MAC scales. We found that age, K6, and fatalism construct in MAC were significantly correlated with total DLQI scores (age: Spearman's ρ= −0.48, P = 0.004; K6: ρ= 0.58, P < 0.001; fatalism; ρ= −0.39, P = 0.025). Conclusions: This is the first study investigating targeted therapy-induced facial skin toxicities in cancer patients. Our results suggest potential negative effects of facial skin toxicities on overall QoL in patients with advanced/recurrent cancer in middle and early old age.